RELATIONSHIP OF LAWS OF LEARNING TO METHODS OF ACCOUNTING INSTRUCTION. - Mitchell, Wiley S. (The Accounting Review, 1963)
Abstract In relation to the comments concerning the laws of learning and their application to accounting instruction, attention will be focused upon some of the learning methods with which accounting teachers are all generally familiar. These methods are commonly labeled teaching methods by many of the people but, for a more proper designation, should be expressed in terms of learning. Too many instructors in their enthusiasm for subject matter either forget or tend to subordinate the role of the student in the learning process. All too frequently one need to be reminded that one is not just teaching subject matter but rather that one is teaching students. It is readily recognized that there is no effective teaching-taking place if leaning does not result. Accounting is a diverse field and covers a wide range of materials, from basic bookkeeping processes to abstract theoretical concepts. This permits and necessitates an equally wide range in educational methodology. To determine the best learning-teaching method to employ is indeed a complex question. The author believes there is no one best way. A variety of methods is no doubt essential within a given course and even a combination of several methods proves most useful within a single class period.